Pengaruh Terapi Story Telling Kisah Nabi Pada Anak Prasekolah Untuk Menurunkan Kecemasan Hospitalisasi - Jumrotun Ni’mah; Ani Ratnaningsih; Akhmad Sayuti (Jurnal Riset Ilmu Kesehatan Umum dan Farmasi (JRIKUF), 2024)
Background: Hospitalization anxiety in children is quite large (60-80%), this is happen if a children had experienced unpleasant events. Hospitalization anxiety needs to be a special concern for health workers because this problem can interfere with the child's growth and development, the healing process and worsen the child's condition. Storytelling therapy for children has many benefits for developing imagination, empathy, establishing closeness, fostering interest in reading and becoming a medium of learning for children. Objective: This research aims to describe the process of providing story telling therapy to preschool aged in anxiety of hospitalization. Method: This study used a case study research design with 2 child patient subjects. The Visual Facial Anxiety Scale (VFAS) measured children's anxiety. This research was conducted in children's rooms at Kardinah Regional Hospital Tegal City. Results: Both research subjects experienced a decrease in hospitalization anxiety. Subject 1 experienced "moderate" became "none" anxiety scale. Subject 2 experienced "moderate high" became "mild" anxiety scale.